Hypoxis hemerocallidea alters metabolic parameters and hepatic histomorphology in streptozotocin-nicotinamide-induced diabetic male rats under antiretroviral therapy - Ismail Olasile Onanuga (Termedia Publishing House, 2019)
Introduction Highly active antiretroviral therapy (HAART) and HIV/AIDS have been demonstrated to induce endocrine/metabolic dysfunction with a consequential increase in morbidity/mortality due to organ toxicities. This study aimed at investigating the possible protective effect of Hypoxis hemerocallidea (HH) against metabolic and hepatic histomorphology of diabetic rats under HAART.